The development of a reliable amateur boxing performance analysis template - Thomson, E.; Lamb, K.; Nicholas, C. (Journal of Sports Sciences, 2013)
The aim of this study was to devise a valid performance analysis system for the assessment of the movement characteristics associated with competitive amateur boxing and assess its reliability using analysts of varying experience of the sport and performance analysis. Key performance indicators to characterise the demands of an amateur contest (offensive, defensive and feinting) were developed and notated using a computerised notational analysis system. Data were subjected to intra- and inter-observer reliability assessment using median sign tests and calculating the proportion of agreement within predetermined limits of error. For all performance indicators, intra-observer reliability revealed non-significant differences between observations (P > 0.05) and high agreement was established (80-100%) regardless of whether exact or the reference value of ±1 was applied. Inter-observer reliability was less impressive for both analysts (amateur boxer and experienced analyst), with the proportion of agreement ranging from 33-100%. Nonetheless, there was no systematic bias between observations for any indicator (P > 0.05), and the proportion of agreement within the reference range (±1) was 100%. A reliable performance analysis template has been developed for the assessment of amateur boxing performance and is available for use by researchers, coaches and athletes to classify and quantify the movement characteristics of amateur boxing.